The Use Of Hip Hop Song In Teaching vocabulary At Muhammadiyah creative 16 Elementary School Surabaya - Febtry Yandary Ayu Kusuma; Amrin Batubara; Linda Mayasari; Waoede Hamsia (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2014)
This study is to find out the implementation of Hip Hop song in teaching vocabulary to students and the advantages of using Hip Hop Song technique to teaching vocabulary. The researcher used qualitative descriptive design. The subjects of this study are both students and teacher at Creative 16 Elementary School Surabaya. The techniques to collect the data were observation and interview. To analyze the data, the adapted interactive model by Miles and Huberman was used. The findingsof the implementation of Hip Hop song in teaching vocabulary are as follows: Opening, Main teaching, and Closing; the advantages of using Hip Hop Song technique are Music motivates the students in the teaching learning process, Listeningto the song improves comprehension skills, Singing songs develops good pronunciation, Singing songs increases vocabulary and speech patterns, Music aids memory, Music brings culture alive, Music acts like a stress buster, Music saves time.